THE PHILIPPINE CHURCH AND POLITICS: A CALL FOR CONSISTENCY - Genilo, Eric Marcelo O. (Asian Horizons, 2020)
The leadership of the Philippine Church uses a dual approach to political engagement. When speaking on social justice issues in the public sphere, the bishops engage the government using modes of discourse consistent with Catholic social teaching principles. However, when speaking out on national issues related to human sexuality and family life, church leaders use a coercive approach. They insist on imposing Catholic teachings on the general population and engage in partisan politics in violation of Church teaching. The inconsistency of the bishops’ dual approach to politics has led to the diminishment of their moral authority and prophetic voice in Philippine society. Unless church leaders adopt a consistent approach to political engagement that recognizes the plurality of faiths in Philippine society and respects the freedom of conscience of all citizens, they will lose their credibility as moral guides in the social and political lives of Filipinos.